Posted by **Diana** on Sunday, June 10, 2007 at 11:24am.

Rewrite the equation -x -6y = -6 as a function of x.

add x to both sides, add six to both sides.

## Answer this Question

## Related Questions

- ALGEBRA - I believe this answer to be correct. Just need to know. -13<= 4x-2&...
- Pre Algebra - Here is another one I need help with. -5x+20=-60 ( remember it is ...
- Algebra - v-6<35 add six to both sides. first you take the 6 and bring it ...
- algerbra 1 - what is the answer to 5x-16=14-5x Just giving you the answer is not...
- math-calculus - so with this one i do the same thing multiplying what inside ...
- Math - Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + ...
- algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...
- science - rearrange this equation 2 make x the subect. 6y = 9 - 3x so first i ...
- Algebra - 89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, ...
- maths - i have to make y the subject of this equation: 4t + 7y - 9 = 0 wod it be...

More Related Questions